Organizational Commitment as The Black Box to Connect the Islamic Work Ethics and Employees Behavior toward Organizational Change - Wartini, Sri; Harjiyanti, Wahyu (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2014)
The objective of the study was to examine the direct and indirect influences of Islamic work ethics on employees behavior toward organization change with organizational commitment as mediation. The population of the study was Public Civil Servants of the general inspectors of finance ministry. The samples were taken by Solvin method. It was a purposive sampling with 87 respondents. The results of the study showed that there was a direct influence of Islamic work ethics on organizational commitment, there was not any direct influence of organizational commitment on employees behavior toward organizational change, there was an indirect influence of Islamic work ethics on employees behavior toward organization change with organizational commitment as the mediation. It is concluded that there were a direct and an indirect influences of Islamic work ethics on employees behavior toward organizational commitmen as the mediation.